The technique of fourth jejunal artery-based jejunal conduit for oesophagojejunostomy after thoracolaparoscopic oesophagogastrectomy for locally advanced Siewert type II tumour - Gopalakrishnan, Gunasekaran (J Minim Access Surg, 2021)
BACKGROUND: Locally advanced long Siewert type II tumor requires total gastrectomy and D2 lymphadenectomy with distal esophagectomy and mediastinal lymphadenectomy for curative resection. In this scenario, a laparoscopic transhiatal approach is not feasible, and the conventional left thoracoabdominal approach is associated with increased morbidity. AIMS AND OBJECTIVES: To describe a novel technique of fourth jejunal artery based jejunal conduit for thoracoscopic esophagojejunostomy after laparoscopic esophagogastrectomy. MATERIALS AND METHODS: The laparoscopic total gastrectomy with distal esophagectomy specimen is extracted through the periumbilical incision. A pedicled jejunal conduit based on the fourth jejunal artery is prepared, and the jejunal conduit is placed in the mediastinum under laparoscopic guidance. Using the thoracoscopic approach in a prone position, additional esophageal clearance and subcarinal lymphadenectomy are performed. Handsewn end to side esophagojejunostomy is performed at the level of the carina. RESULTS: Three patients with long Siewert type II underwent this procedure after neoadjuvant chemotherapy. None of the patients had conduit related complications. All three patients had abdominal lymph node involvement and two patients had mediastinal lymph node involvement. CONCLUSION: Pedicled jejunal conduit based on the fourth jejunal artery is safe for intrathoracic anastomosis after minimally invasive esophagogastrectomy for locally advanced Siewert type II tumor.